Evaluation of eating habits of nursing and midwifery department first class girl of university students - Lok, Neslihan; Kocak Uyaroglu, Arzu (Innovational: Journal of Nursing and Healthcare, 2024)
Objective: This study was cross sectionally carried out in order to evaluate the eating habits of female students in the first year of nursing and midwifery department in accordance with the related factors. Material and methods: All of the first grade female students at Selcuk University, faculty of medical sciences, nursery and midwifery department in konya province were included the study. A total of 151 female students who agreed to participate in the study constituted the study group. During the collection of data, a questionnaire form that has been developed by the researchers and investigates the socio-demographic characteristics and eating habits and the hexade likert type Eating Attitudes Test (EAT) and used to measure possible eating disorders that exist in normal people. For the analysis of data Chi-square test and t test were used. Results: The average age of the students was found as 18.63±1.105 and that of the Body Mass Index (BMI) as 20.8980±2.85916. Those who received criticism about their bodies and their average YTT scores were found lower and the difference was statistically meaningful (x2=6.771, p=0.009). when the relationship between BKI and eating behaviors is considered, possible eating disorders of people with normal kilos was significantly high (x2=12.347, p=0,002). Conclusion: As a result, being at a normal weight and body likely to receive criticism about the eating disorder can be defined as the risk group. Therefore, screening for possible eating disorder should be done regularly explained the importance of nutrition and preventive measures should be taken.